Levels of persistent organic pollutants and residual pattern of DDTs in small cetaceans from the coast of São Paulo, Brazil - Yogui, G. T.; Santos, M. C. O. [UNESP]; Bertozzi, C. P.; Montone, R. C. (Pergamon-Elsevier B.V. Ltd, 2010)
The State of São Paulo is the most developed area in Brazil and was impacted by persistent organic pollutants for several decades. This study investigated organochlorines in five species of small cetaceans (Pontoporia blainvillei, Stenella frontalis, Sotalia guianensis, Tursiops truncatus and Steno bredanensis) found dead along the coast of São Paulo between 1997 and 2003. DDTs (15.9 mu g g(-1) lipid: mean for all pooled individuals) and PCBs (8.08 mu g g(-1)) exhibited the highest concentrations in the animals, reflecting large amounts formerly used in Brazil. Lower levels of mirex (0.149 mu g g(-1)), HCB (0.051 mu g g(-1)), CHLs (0.008 mu g g(-1)) and HCHs (0.007 mu g g(-1)) were detected in all species. Residual pattern of DDTs in dolphins suggests that o,p'-DDT is more recalcitrant than p,p'-DDT in the body of the animals and/or the environment. In contrast to p,p'-DDT, residues of o,p'-DDT seem to be preferentially converted into o,p'-DDD rather than op-DDE. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Chlorinated hydrocarbons; Sotalia guianensis; Pontoporia blainvillei; Stenella frontalis; Tursiops truncatus; Steno bredanensis